Better for Whom? Leveling the Injustices of International Conferences by Moving Online - Niner, Holly J.; Wassermann, Sophia N. (Frontiers in Marine Science, 2021)
International conferences are an important component of the professional calendar of scientists and practitioners in many fields, and are valued as opportunities to establish, create and foster networks, wellbeing and knowledge. The 2020 global pandemic, in prohibiting large gatherings and travel, has provided an opportunity to test the feasibility and implications of a shift from in-person to online conference formats. Avoiding international travel and associated bureaucracy, time and expense could overcome many of the historic injustices preventing many from participating in and benefiting from international conferences, and also avoid the emissions associated with international air travel. However, prior to 2020, there has been resistance to moving these events online because of the perception that the value of conferences cannot be cultivated online. Here, we use the example of the 6th International Marine Conservation Congress (IMCC6), which moved online in response to the COVID-19 pandemic, to explore participants’ perceptions and experiences of an online conference and the potential effects on access and inclusion. Our results show that moving online substantially increased the accessibility of the conference for those who would be unable to attend an in-person event for financial or personal reasons. Results also indicate that the online experience was able to recreate some of the benefits of in-person events, and that many participants are interested in attending online or virtual events in the future. However, the degree of enjoyment experienced or perceived ‘value’ likely relates to the frame of reference of the individual participant and a commitment to actively engage in the program. Reflecting on the success of IMCC6, we conclude that holding international conferences online, or at least including an online element as part of a ‘hybrid’ model, is a significant improvement in the capacity of conferences to meet the moral imperatives of the conservation community by addressing the climate crisis and some of the systemic injustices within the field.